The assessment of blood cortisol and creatine kinase concentration in personalizing the football players training - Gala-Bladziñska, A.; Przednowek, K.; Czaja, R.; Czarny, W.; Król, P.; Kotarska, K.; Nowak, L.; Pasko, W.; Bajorek, W. (Acta Kinesiologica, 2022)
Background: Blood tests are a common health assessment for diagnosing diseases and bodily disorders. Aims: The aim of the work was to analyze the suitability of sampling and assessing athletes` blood-borne biomarkers in a search for ways to optimize their football training. Methods: In the prospective study, the results of 14 football players from a youth football team competing at the highest national level `blood tests were evaluated before (P1), immediately after (P2) and 24 hours after (P3) playing a football match. The all players were divided into two groups based on the length of time they were on the field during the game: FMP - (8 players) participation in the match for 90 minutes, and PMP - (6 players) participation in the match for 30-75 minutes. Results: In the FMP group, at P2, the following statistically significant (p<0.001) differences were observed: an increase in the leukocyte count; decreases in erythrocytes (RBC), hemoglobin (HGB), and hematocrit (HCT), and increases in creatine kinase (CK), cortisol and lactates. At P3 when comparing the FMP and PMP group results, we observed an increase in CK (p=0.03) and decrease in cortisol (p=0.02) in the former group. The concentration of cortisol<356.04nm/L at P3 was the most sensitive and specific (PPV=0.83; NPV=0.88) difference characterizing the group of FMP players compared with the players of the PMP group. In the FMP group compared with PMP at P3 we showed a significantly increased levels of CK (p=0.002). Conclusions: The blood cortisol levels below 356.04nm/L and CK concentrations below 500UI/L taken 24 hours after the football game in the players from a youth football team competing at the highest national level are characteristic of players with a greater potential for physical exercise.